On the maximal number of cubic runs in a string - Crochemore, M.; Iliopoulos, Costas; Kubica, M.; Radoszewski, J.; Rytter, W.; Walen, T. (Springer, 2010)
A run is an inclusion maximal occurrence in a string (as a subinterval) of a repetition v with a period p such that 2p =|v|.The maximal number of runs in a string of length n has been thoroughly studied, and is known to be between 0.944 n and 1.029 n.In this paper we investigate cubic runs, in which the shortest period p satis?es 3p =|v|. We show the upper bound of 0.5 n on the maximal number of such runs in a string of length n, and construct an in?nite sequence of words over binary alphabet for which the lower bound is 0.406 n.